Modelling the Effect of Applied Voltage and Frequency on Electroluminescence in Polymeric Material - N.A. Bani; Z Abdul-Malek; F Muhammad-Sukki; A Abubakar Mas’ud; M.N. Muhtazaruddin; K Kamardin; J.J. Jamian; H Ahmad (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Electroluminescence method has been used by several researchers to observe the behaviour of an aged polymeric material. Electroluminescence is a phenomenon that occurs when the atoms of a material are being excited due to the application of and external high electrical stresses. The changes in the energy level of these excitation states can be used as an indicator for the initiation of electrical ageing. There are several factors that affect the behaviour of electroluminescence emission such as, among others, applied voltage, applied frequency, ageing of material and types of materials and gases used are discussed in this paper. A mathematical approach relating these factors and the intensity of electroluminescence is proposed through the aid of Dimensional Analysis method. A close relationship is obtained between experimental and simulation that suggests this mathematical approach can be utilized as a tool to predict electrical ageing of insulation material.